Plant hairy roots enable high throughput identification of antimicrobials against Candidatus Liberibacter spp. - Sonia Irigoyen (Nature Portfolio, 2020)
The putative causal agent of citrus greening Candidatus Liberibacter asiaticus (CLas) cannot be cultured, which hampers finding new therapies to control this devastating disease. Here, the authors show that hairy roots support CLas propagation and enable high throughput antimicrobial screening.